A meta-analysis of the pique technique of compliance. (2nd January 2017) - Lee, Seyoung; Feeley, Thomas Hugh
Abstract: A random-effects meta-analysis was undertaken to examine the effectiveness of the pique technique of compliance-gaining. Results indicated an overall significant effect of the pique technique on increased compliance rate across 17 comparisons ( r = .27). Moderator analyses showed the technique worked significantly better than controls in gaining compliance when a smaller amount was requested, when the reason for the request was included, and when the technique was used in France. In addition, the pique technique was more successful than control requests in terms of the total amount of money or time given by participants and the percentage of participants inquiring about the requests. Theoretical and practical implications for the success of pique technique are discussed for future research.